(untitled) (Estudios de Historia de España, 2016)
In the present work we set out to approach some aspects related to the restrictions, the privileges and the violence, that were implemented on mudéjares of Castile, Aragón and Valencia. In relation to first, we will give account of the legal hardening - real and ecclesiastical that unfolded towards the Hispanic Moors and who regulated almost all the aspects of daily living and of its religious practices. Nevertheless, mudéjares and their mosques in some area in individual, were subject of real privileges. It is by that we will analyze restrictions and privileges like two faces of a same process that unfolded during the transit of the low middle age. Finally, we will investigate on the episodes of violence towards mudéjares resisting regional particularitities, to connect these events with the segregation and the restriction.